Gender-based comparison of takotsubo syndrome versus myocardial infarction - Giannakopoulos, Konstantinos; El-Battrawy, Ibrahim; Gietzen, Thorsten; Ansari, Uzair; Borggrefe, Martin; Akın, Ibrahim (QJM, 2019)
Background: Takotsubo Syndrome (TTS) is an acute reversible left ventricular dysfunction. Recently published studies have highlighted a similar mortality rate as acute coronary syndrome (ACS). We compared the impact of gender differences on the outcome of TTS patients as compared to ACS patient.